KERJASAMA PERTAHANAN INDONESIA - INDIA DI KAWASAN SAMUDRA HINDIA - Zurian, Irma; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of research to determine crimes that occurred in the Indian Ocean region during the 5 years starting from 2018-2022, as well as cooperation and implementation of defense cooperation in the region. The Indian Ocean is a strategic water area which has a main purpose for the world economy. This ocean functions as a link for international trade routes from Asia to Europe or vice versa. Critical trade routes are the Strait of Malacca, the Strait of Hormuz and the Bab el-Mandeb. Therefore, many crimes occur in these waters, such as transnational crimes, terrorism and border disputes. Method used is descriptive with a qualitative approach. Data collection techniques using library research. The theory used to answer this research is maritime security theory by Natalie Klien, with indicators for management, development and protection of marine resources. The perspective used is liberalism, with a nation state level of analysis. Based on the research result that the cooperation carried out by Indonesia and India has collaborated in various fields such as dealing with transnational crime, terrorism and determining regional boundaries. These efforts are gathered within the IORA organization. However, this has not been fully implemented well. This happened because of the extradition agreement's lack of understanding by the implementing authorities in carrying out extradition. In preventing terrorism financing, there is still a lack of supervision over the flow of domestic funds. Meanwhile, the determination of the exclusive economic zone is still often violated by fishermen because the territorial boundaries are large, so that few fishermen or the community around Rondo Island in Aceh know their territorial boundaries. Keywords: IORA, Indian Ocean, Maritime Crimes, Maritime Security.